Academic stress at different yearsof study - Sabirova, R.Sh.; Umurkulova, M.M.; Kuo, Ben C.H. (KU publ., 2020)
The article describes the results of a study of academic stress in 119 psychology students of the Faculty of Philosophy and Psychology of Karaganda State University. The author substantiates the relevance of the stress problem arising in the process of educational activity. The necessity of enriching the diagnostic arsenal of psychologists and teachers with new methods for academic stress research is shown. An empirical study identified objective and subjective sources, mental and somatic manifestations of stress. The dynamics of the course of academic stress at different stages of study at the university is revealed. The results obtained by the authors of the article demonstrate the greatest severity of all parameters of physical and psychological distress at first and fourth years of study. The non-adaptive nature of coping strategies used by students of different grades to stop the negative psycho-emotional experiences associated with stress in educational activities is disclosed. The necessity of psychological and pedagogical support of students in situation of academic stress is shown. The general characteristic of the support program developing personality resources of the students is given, taking into account new methodological approaches to skills and learning strategies.
Əр түрлі оқу жылдарындағы академиялық стресс
Академический стресс в разные годы обучения
Keywords: academic stress; stress dynamics; coping behavior; coping; students' mental health; stress diagnostics; educational activities; support; training skills; resource approach